The Influence of Financial Indicators, Corporate Governance and Macroeconomic Variables on Financial Distress - Candradewi, Made Reina; Rahyuda, Henny (Jurnal Ekonomi Kuantitatif Terapan, 2021)
This study aims to analyze the effect of financial indicators, corporate governance and macroeconomic variables on financial distress in manufacturing industry companies listed on the Indonesia Stock Exchange (IDX). This research is expected to provide solutions and insight to the companies in tackling financial distress. In addition, this research is expected to enrich knowledge about the influence of financial indicators, corporate governance, macroeconomic variables on financial distress. This research is conducted using a quantitative approach. The population in this study are all manufacturing industry companies listed on the Indonesia Stock Exchange in the period of 2016-2018. The sampling technique is purposive sampling method and the final sample in this study is 136 companies. The main findings of the study show that liquidity ratio has a negative and significant effect on financial distress, leverage ratio has a positive and significant effect on financial distress, activity ratio has a negative and significant effect on financial distress and the size of the board of directors has a negative and significant effect on financial distress.